IN VITRO STUDY, CORROSION, AND THERMAL OXIDATION BEHAVIOR OF WIRE-SHAPED NITISN SHAPE MEMORY ALLOY - Qader, Ibrahim Nazem; Kok, Mediha; Cirak, Zehra Deniz; Pekdemir, Mustafa Ersin; Saydam, Sinan; Aydogdu, Yildirim (World Scientific Publ Co Pte Ltd, 2021)
The development of NiTi-based shape memory alloys (SMAs) for some medical applications has been limited by releasing Ni element into the organic tissue. In this study, Ni47Ti50Sn3-wire (at.%) SMA was produced using the arc-melting technique, and the alloy was subjected to non-isothermal processes. Some characteristics of the alloys, such as oxidation behavior, corrosivity, and in vitro study in simulated body fluid and physiological solution at body temperature, were investigated. The corrosion rate of the as-casted alloy was lower than the equiatomic-NiTi alloy found in the literature. The estimated ICP-MS results showed that the release of alloying constituents into the solutions is in accordance with the standards.
Keywords: NiTiSn; wire-shaped shape memory alloy; oxidation; TiO2; corrosivity; in vitro